The knowledge of menopause and its treatment among orang Asli in Gombak - Mohamad Diah, Nurazzura (s.n, 2012)
Menopause is a time of life where women make the transition from a reproductive stage to a non-reproductive stage. Although it is biologically universal, menopause experiences are not homogeneous in nature and there have been significant differences reported by women within and across culture. The objective of this study is two-fold: to investigate the prevalence of menopausal symptoms among Orang Asli and to identify ways how they treat their menopausal symptoms